Generalised space vector PWM for sinusoidal output voltage generation with multiphase voltage source inverters. (20th May 2009) - Dujic, Drazen; Jones, Martin; Levi, Emil
The paper presents a generalised approach towards the development of the space vector pulse width modulation (SVPWM) for sinusoidal output voltage generation with two-level multiphase voltage source inverters (VSIs), where the number of phases is an odd number. The generalisation can greatly speed up the implementation since the tedious analysis of 2n voltage space vectors of an n-phase inverter in the corresponding (n − 1)/2 2-D planes can be completely avoided. Required dwell times for active space vectors are correlated with trigonometric properties of multiphase systems, which account for the actual phase number. Feasibility of the developed approach has been verified experimentally using the five-phase and seven-phase SVPWM schemes as examples.